Your memory, a user's guide - Baddeley, Alan D., 1934- (Harmondsworth, Middlesex : Penguin, 1982)
A noted researcher explains the latest findings on how memory works and provides numerous easy-to-use tech- niques that will help improve various aspects of memory retention, including the verbal, numerical, visual, and spatial.
Includes bibliographical references and index.
Keywords: Memory